CommunityCORE: bookmobile and lunchbox : an exercise in rural engagement - Allen, Zev A. (My University, 2015)
A relative of mine always used to say, "God gave people hands, so that they can help themselves." While that statement was made with the intent of instilling a sense of work ethic in a formative child, it also charged me with the eye to see and wonder why some never seemed able to help themselves. As time went on I began to understand that we are more affected by the situations that we are born into than the opportunities that we create for ourselves. It was with this realization that I could fully appreciate the situation and contribution that all persons are capable of, given the proper chance. Bookmobile and Lunchbox seek to nurture the life-chances of rural northern Jackson County, and unearth the potential of its citizenry. It is with this in mind that I revise the phrase to, "God gave people hands, so that they can lend them to a neighbor."
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Allen, Z. A. (2014). CommunityCORE bookmobile and lunchbox : an exercise in rural engagement. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Community CORE Foundation; Rural development--Kansas--Jackson County; Bookmobiles--Kansas--Jackson County; Food relief--Kansas--Jackson County; Reports; Reports